2011
DOI: 10.1016/j.geomorph.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Object representations at multiple scales from digital elevation models

Abstract: In the last decade landform classification and mapping has developed as one of the most active areas of geomorphometry. However, translation from continuous models of elevation and its derivatives (slope, aspect, and curvatures) to landform divisions (landforms and landform elements) is filtered by two important concepts: scale and object ontology. Although acknowledged as being important, these two issues have received surprisingly little attention.This contribution provides an overview and prospects of objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(47 citation statements)
references
References 71 publications
0
46
0
1
Order By: Relevance
“…The basic principles of applying the ALV method are illustrated in Figure 2 [19,27,28]. When the grid size is small enough, some adjacent grid cells belonging to the same class express the same population distribution patch.…”
Section: Alv Methods Application Principlesmentioning
confidence: 99%
“…The basic principles of applying the ALV method are illustrated in Figure 2 [19,27,28]. When the grid size is small enough, some adjacent grid cells belonging to the same class express the same population distribution patch.…”
Section: Alv Methods Application Principlesmentioning
confidence: 99%
“…Various automated procedures are available for discretising river networks into homogeneous reaches or spatial units based on morphological attributes, such as change point detection using the Pettitt test [133] or image segmentation partitioning [134][135][136]. The global zonation scheme of Gill [137], for example, is an aggregation routine based on analysis of variance which iteratively breaks a sequence of values into zones that are as internally homogeneous and as distinct as possible from adjacent zones (for a summary, see [138]).…”
Section: The Auditing Processmentioning
confidence: 99%
“…However, they depend on arbitrary choices of shape parameters and the scale value. Hence, in [24], the authors suggested to use ontologies to relate landform concepts and the segmented objects and discussed the need for conceptual models for semantic-based classification.…”
Section: Object-based Image Analysismentioning
confidence: 99%
“…In order to deal with specific geomorphometry, Drȃguţ and Eisank [24] introduced the concept of discrete geomorphometry, stating that objects obtained from segmentation could be used as intermediate building blocks to form larger landform divisions. Landforms would be first delineated and then classified.…”
Section: Application To Specific Geomorphologymentioning
confidence: 99%